In situ synthesis and deposition of gold nanoparticles with different morphologies on glass and ITO substrate by ultrasonic spray pyrolysis - De la Garza, María; López, Israel; Gómez, Idalia (Hindawi Publishing Corporation, 2013)
Gold nanoparticles were synthesized and deposited in situ by ultrasonic spray pyrolysis on glass and indium tin oxide (ITO) substrates. This technique led to the formation of gold nanoparticles with different morphologies without the use of any capping agent. The gold nanoparticles deposited on glass substrate were obtained as nanospheres with an average particle size of 30 nm with some agglomerates; however, the nanoparticles deposited on ITO substrate were obtained with different morphologies, such as triangular nanoprisms, nanorods, nanocubes, and nanorhombus, with particle sizes between 40 and 100 nm. The ITO substrate influenced the morphology of the gold nanoparticles obtained due to changes in the deposition temperature, which also change the crystalline structure of the ITO film on the substrate.